Contract farming, contract design and smallholder livelihoods* - Anette Ruml; Catherine Ragasa; Matin Qaim (Australian Journal of Agricultural and Resource Economics, 2021)
Contract farming has gained in importance in many developing countries. Previous studies analysed effects of contracts on smallholder farmers' welfare, yet mostly without considering that different types of contractual relationships exist. Here, we examine associations between contract farming and farm household income in the oil palm sector of Ghana, explicitly differentiating between two types of contracts, namely simple marketing contracts and more comprehensive resource-providing contracts. Moreover, we look at different income sources to better understand how both contracts are linked to farmers' livelihood strategies. We use cross-sectional survey data and regression models. Issues of endogeneity are addressed through measuring farmers' willingness-to-participate in contracts and using this indicator as an additional covariate. Farmers with both types of contracts have significantly higher household incomes than farmers without a contract, yet with notable differences in terms of the income sources. Farmers with a marketing contract allocate more household labour to off-farm activities and thus have higher off-farm income. In contrast, farmers with a resource-providing contract have larger oil palm plantations and thus higher farm incomes. The findings suggest that the two contract types are associated with different livelihood strategies and that disaggregated analysis of different income sources is important to better understand possible underlying mechanisms.
Keywords: 330; contract farming; credit schemes; Ghana; household income; off-farm income; oil palm